The role of journalistic voice in communicating climate scepticism. (July 2022) - Grien, Angelina; MacNeil, Robert
This brief study investigates the subtle ways that language can be used to subconsciously shape a reader's opinions about climate science within conservative news texts. To do so, our study employed techniques from critical discourse analysis to highlight the role of 'journalistic voice' and consider the granular linguistic techniques these outlets may use to subliminally validate sceptical viewpoints, while casting doubt on those espousing the consensus position. We found that certain semantic structures used in conservative climate reporting can take an otherwise apolitical analysis of climate issues, and potentially guide readers to a reactionary conclusion. Our analysis arrived at this position after undertaking a critical discourse analysis of the ways in which sceptical and non-sceptical climate 'experts' have been framed by Australia's largest conservative broadsheet newspaper, News Corp's The Australian, in the period after it changed its official position on climate to one of accepting the consensus view.